Reputation, accounting information and debt contracts in Chinese family firms - Hao Li (China Journal of Accounting Research, 2010)
This paper provides evidence to show that in the presence of imperfect formal institutions there is both a substitutional and a complementary relationship between accounting information and reputation, an informal institution. Empirical results using a sample of family firms listed in the Chinese A-share stock market from 2004 to 2007 show that in China, where the legal environment is far from perfect, the complementary relationship between reputation and accounting information is more pronounced than is the substitutional relationship. Thus, the aggregate effect is that a better reputation improves the usefulness of accounting information in debt contracts. Besides the aggregate effect, this paper also provides evidence of the substitutional and complementary relationships between reputation and accounting separately.
Keywords: G14; G32; M41; 650; Reputation; Family firm; Accounting information; Debt financing; Contracting cost